Novos Fósseis de Vertebrados para a Sanga da Cruz (Pleistoceno Superior), Alegrete, RS, Brasil - KERBER, LEONARDO; OLIVEIRA, ÉDISON V. (Pesquisas em Geociências, 2008)
New specimens of Glyptodon sp., Morenelaphus sp., Pampatherium typum and Testudines indet. from the outcroup Salatiel II, Sanga da Cruz, Alegrete, State of Rio Grande do Sul, are reported. The fossils are represented by long bones and isolated and articulated osteoderms. The fossil material comes from conglomerate sandstones assigned to the latest Pleistocene (Lujanian age). The reported absolute dates for the Sanga da Cruz are in according to the Lujanian age, but the reworking evidences coupled with the wide temporal range of the reported Pleistocene taxa disables a better correlation and a paleoecological interpretation.